STATUS GIZI BALITA DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) - Novi Enis Rosuliana (STIKES Mataram, 2019)
Nutritional status in toddlers is part of the individual factors of children who play a role in the course of acute respiratory infections (ARI). Poor nutritional status has an impact on reducing the status of immunity so that it is susceptible to infectious diseases. The purpose of this study was to determine the relationship of nutritional status of infants to the incidence of acute respiratory infections (ARI). This study uses an observational research design with a cross sectional approach. The population in this study was 825 toddlers with a total sample of 89 respondent toddlers, using quota sampling. As for data analysis using the chi square test. The results of data analysis obtained that most respondents had good nutritional status of 44 (49.4%) while for the ISPA incidence of 50 (56.2%) with p value was 0.001 indicating p value